A view on spinning - induced rhabdomyolysis - Vasques, Marco Agassiz Almeida; Gomes, Leani Falcão (Revista de Medicina e Saúde de Brasília, 2019)
The practice of indoor cycling (spinning) may lead to exertional rhabdomyolysis, a potentially severe condition that often needs hospitalization and intravenous hydration to prevent complications such as acute renal failure. The literature on this subject is predominantly of series and case reports. This article consolidates the data of 92 cases of spinning induced rhabdomyolysis (SIR) published up to 2018. There was a predominance of cases in young female initiating the practice. The average duration of the session was 50 minutes. The symptoms of myalgia (73%), muscle weakness (33%), dark urine (32%) and muscle swelling (27%) were the most reported in the patients. The onset of symptoms occurred in 2 days (average) after exercise (range 0- 8 days). Levels of serum creatine kinase on admission were between 4,676 and 261,177 IU/L (average 56,869); AST ranged from 122 to 4,170 IU/L (average 1,237), ALT ranged from 56 to 2,583 IU/L (average 444), and LDH levels were from 834 to 62,970 IU/L (average 6,112). Muscles most frequently involved were quadriceps muscles. Acute renal failure was reported in 8 cases and compartment syndrome in 4 patients. Knowledge on the physiopathology of this disease has implications on preventive measures, especially on educational aspects directed towards agents involved in physical activity.